THE EXPERIENCE IN THE EDUCATIONAL PROCESS TRAINER IN: FROEBEL, FREINET E DEWEY. - Ana Paula Ennes de Miranda Eto; Nicanor Palhares Sá (Reflexão & Ação, 2011)
This study presents the characteristics and concepts of the Active New School and an active school of thought from some intellectual education: Froebel, Dewey and Freinet. Contributes to the understanding of how the experience and other escolanovista precepts were addressed and appropriate within the educational thought of these three intellectual educations. The paper presents considerations for education and active school in order to expose ideas about the school context in the view of these intellectuals based on aspects that characterize these works. The text begins with Froebel, based on the reference treatment unit called Vital. Then Freinet presents, seeing their thoughts about the French Popular School, heading to Dewey in his thought and association between school and life.